Cardiovascular and ventilatory limitations in the oxygen transport pathway - Padilla, Danielle Jessica (Kansas State University, 2005)
The components of the O2 transport pathway can be divided into (along with their respective circulations) the pulmonary, cardiovascular, and skeletal muscle systems. They must operate in tight conjunction with one another, especially during dynamic exercise, to sustain ATP production within muscle mitochondria. Any limitation placed on the O2 transport pathway will result in decreased performance. The purpose of this dissertation is to present four novel studies which examine specific limitations on (1) the pulmonary system (i.e. lungs and circulation) within the highly athletic Thoroughbred horse (Studies A & B), and (2) within the peripheral circulation (i.e. microcirculation) within a disease model of Type II diabetes, the Goto-Kakizaki (GK) rat (Studies C & D). Study A demonstrates that locomotory respiratory coupling (LRC) is not requisite for the horse to achieve maximal minute ventilation (VE) during galloping exercise because VE remains at the peak exercising levels over the first ~13 s of trotting recovery (VE at end exercise: 1391±88; VE at 13 s: 1330±112 L/sec; P > 0.05). The horse also experiences exercise-induced pulmonary hemorrhage (EIPH) which has been linked mechanistically to increased pulmonary artery pressure (Ppa) during high intensity exercise. Therefore, in Study B, we hypothesized that endothelin-1 (ET-1), a powerful vasoconstricting hormone, would play a role in the augmented Ppa and therefore, EIPH. However, contrary to our hypothesis, an ET-1 receptor antagonist did not decrease Ppa nor prevent or reduce EIPH. Studies C and D examine potential mechanisms behind the exercise intolerance observed in humans with Type II diabetes. Utilizing phosphorescence quenching techniques (Study C) within the GK spinotrapezius muscle, we found lowered microvascular PO2 (PO2mv; Control: 28.8±2.0; GK: 18.4±1.8 mmHg; P<0.05) at rest and a PO2mv “undershoot” during muscle contractions. After conducting intravital microscopy within the same muscle (Study D), we discovered the percentage of RBC-perfused capillaries was decreased (Control: 93±3; GK: 66±5 %; P<0.05) and all three major hemodynamic variables (i.e. RBC velocity, flux, and capillary tube hematocrit) were significantly attenuated. Both studies (C & D) indicate that there is reduced O2 availability (via decreased O2 delivery; i.e. ↓QO2/VO2) within Type II diabetic muscle.
Keywords: Rat; Phosphorescence quenching; Microcirculation; Locomotor respiratory coupling; Biology, Animal Physiology (0433); Health Sciences, Health Care Management (0769); Health Sciences, Pathology (0571)